2019
DOI: 10.1111/jcmm.14468
|View full text |Cite
|
Sign up to set email alerts
|

Sodium (±)‐5‐bromo‐2‐(α‐hydroxypentyl) benzoate ameliorates pressure overload‐induced cardiac hypertrophy and dysfunction through inhibiting autophagy

Abstract: Sodium (±)‐5‐bromo‐2‐(a‐hydroxypentyl) benzoate (generic name: brozopine, BZP) has been reported to protect against stroke‐induced brain injury and was approved for Phase II clinical trials for treatment of stroke‐related brain damage by the China Food and Drug Administration (CFDA). However, the role of BZP in cardiac diseases, especially in pressure overload‐induced cardiac hypertrophy and heart failure, remains to be investigated. In the present study, angiotensin II stimulation and transverse aortic constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…More recent reports have overwhelmingly supported that myocardial ALP insufficiency results from chronic pressure overload and contributes to maladaptive cardiac remodeling and heart failure [4,20]. Several studies indicated that increased LC3II expression exists in cardiomyocytes under Ang II stimulation [21], in this condition, reducing LC3II, which presenting reducing the autophagosomes, may play protective role in Ang II-induced injury. We speculated that when there is an ALP insufficiency, reducing the numbers of autophagosomes may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…More recent reports have overwhelmingly supported that myocardial ALP insufficiency results from chronic pressure overload and contributes to maladaptive cardiac remodeling and heart failure [4,20]. Several studies indicated that increased LC3II expression exists in cardiomyocytes under Ang II stimulation [21], in this condition, reducing LC3II, which presenting reducing the autophagosomes, may play protective role in Ang II-induced injury. We speculated that when there is an ALP insufficiency, reducing the numbers of autophagosomes may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that autophagy is able to regulate cardiac oxidative stress, hypertrophy, and apoptosis. Hyperactive or dysfunctional autophagy plays a key role in the transition from stable cardiac hypertrophy to decompensated heart failure [ 19 , 20 ]. Therefore, we investigated the effects of downregulating miR-128 on cardiomyocyte autophagy in vivo and in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…33 Previous studies indicate that inhibiting excessive cardiac autophagy contributes to the prevention of cardiac hypertrophy. [34][35][36] Other studies show that autophagy is only slightly elevated for several days after TAC surgery and that enhancing autophagic flux can benefit the heart by helping it adapt to long-term pressure stimulation. [37][38][39] Although the role of autophagy is controversial, we found that it was significantly activated in both TAC and Ang II-induced cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%